Breast cancer in Portugal: an epidemiologic analysis of incidence, survival, mortality and hospital admissions - Gomes, Inês Afonso (2020)
ABSTRACT - Background: Breast cancer (BC) is the most common malignancy and cancer-related death cause in Portuguese women and represents a high burden in nowadays society. The BC incidence and mortality rates have been growing in our country, parallelly with an increase in survival and a rising demand on the health system by these patients. Aim: This work aimed to epidemiologically characterize, assess the evolution and the association between BC incidence, use of breast cancer-related healthcare services and their outcomes in Portuguese women, namely their mortality and survival. Methods: A descriptive analysis, followed by data mapping, spatiotemporal analysis and spatial variations in temporal trends analysis was conducted. Additionally, a Kaplan Meier survival analysis was performed in this study to estimate overall survival (OS). Results: In the studied period, the crude incidence (Southern Portugal, 2005-2012), hospitalization (2002-2016) and mortality (2002-2013) rates reached 119.3, 118.72 and 28.47/100,000 females, respectively. Additionally, the median OS was 112 months (cumulative survival at 1/3/5 years: 94.9%/85.6%/76.5%) among women diagnosed with BC in 2005-2012 in the Southern region of the country. A stratified analysis per demographic, clinical and context characteristics, namely age and stage at diagnosis, as well as place of residence, also showed asymmetries in these indicators. The crude BC incidence rate (IR) in Southern Portugal was higher in older women (17.7, 156.9, 213.3 and 232.9/100,000 inhabitants for women diagnosed at <40, 40-49, 50-64 and ≥65 years), a trend similar to that reported for the nationwide mortality rate (MR) (5.9, 40.7, 14.1 and 84.6/100,000 females for those aged <50, 50-64, ≤64 and ≥65 years). In this study conducted among Southern Portuguese women, the median age at BC diagnosis was 60.84 years, with a predominance of locoregional (78.4%), unspecified location (44.5%) and ductal carcinoma (73.1%) cases. Most of BC incident cases (50.5%) were located in the Lisbon region, with a higher IR being described for locoregional disease at diagnosis versus their metastatic counterparts (93.6 vs 7.4/100,000 females). Additionally, a metastatic stage at BC diagnosis was associated with demographic (age at diagnosis ≥ 50 years), clinical (lobular and 'other' morphologies, unspecified location) and contextual (place of residence) characteristics. In this study, the nationwide hospitalizations with a main BC code consisted mostly of programmed (81.2%), surgical admissions (85.5%) in women aged 50-64 (36.2%) and ≥ 65 years (37.7%) of age, showing a median length of stay of 5 days and a 5.5% in-patient lethality. The median OS reported in the BC patients diagnosed in the South of the country in 2005-2012 was higher among those diagnosed at a locoregional stage (median OS: 115 vs. 31 months for metastatic patients, p<0.001; cumulative survival at 1/3/5 years: 96.8%/89%/80.5% vs 70.4%/42.9%/28.1%) and at a younger age (18, 129, 124 and 87 months for women <40, 40-49, 50-64 and ≥ 65 years of age at diagnosis). The findings of this work further indicate a spatial and temporal heterogenicity in the BC incidence, survival, mortality and hospitalizations among Portuguese women, with the detection of numerous temporal (incidence, hospitalization, mortality), spatiotemporal (incidence, hospitalization, mortality) and spatial-variations in temporal trends (incidence, hospitalization) clusters. Most of the high spatiotemporal clusters were reported in Lisbon, suggesting the need for further studies in this metropolitan area. Additionally, a growing trend was identified in the IR (4.1 %/year), MR (1.2 %/year), and hospitalization rates (3.109 %/year) over the studied period, with a differential evolution being reported according to the patient’s age (IR: +5.935, +3.833, +4.114 and +2.194 %/year growth in women diagnosed at <40, 40-49, 50-64 and ≥ 65 years of age, respectively; MR: +0.725, - 1.781, - 0.0907 and +0.896 %/year in women aged <50, 50-64, ≤64 and ≥65 years at time of death) and stage at diagnosis (+6.976 and +0.303 %/year, for incident locoregional and metastatic patients, respectively). Despite the parallel evolution of the BC incidence, hospitalization and mortality rates in the Southern area of the country (IR: +4.1%/year, hospitalization rate: 126.5/100,000 females, +1.2%/year, MR: 34.3/100,000 females, +1.6%/year), no correlation (p<0.05) was detected between these at the county level. Conclusions: The growing trends of BC incidence, hospitalization and mortality rates, suggest that further assessments are deemed on the management strategies for this disease among Portuguese women. The differential patterns identified according to age and stage at diagnosis further point to a need to systematically assess these subgroups as separate entities within the BC population. Additionally, this analysis identified high “risk” clusters, namely in the Lisbon area, which can be valuable data sources in the shaping of future oncology health programs. Finally, this effective use of spatiotemporal methods in the identification of outcome trends could be leveraged to other cancers.